Coverage of crime news: content analysis of Al-Yaum Saudi online newspaper - SULIEMAN, H.M (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study aims to answer the question of how Saudi’s Al-Yaum online newspaper covers the crime news, from Jan - Dec 2018. The descriptive method is used, and data is collected through a structured content analysis sheet. 24 versions represent a systematic random sample was analyzed. The results were: Saudi newspapers cover mere internal crime news, the most types of the crime news were cover was the murder, assault, sale of illegal beverages and drugs, and the least published was news dealing with topics of felonious assault, interfering with an officer, contempt of court, and criminal libel.